A stainless steel seamless thin-walled steel pipe and its preparation method

By adding niobium and lanthanum to stainless steel seamless thin-walled steel pipes, combined with laser quenching and corrosion-resistant strengthening coating technology, the problem of balancing strength and corrosion resistance of existing stainless steel pipes is solved, achieving high hardness and excellent performance. Corrosion Resistance Effect.

CN118497640BActive Publication Date: 2025-01-24SHANGHAI KAISITE STEEL PIPE MAKING
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410947046.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-16
Publication Date
2025-01-24
Estimated Expiration
2044-07-16

AI Technical Summary

Technical Problem

Existing stainless steel seamless pipes are difficult to take into account between high strength and corrosion resistance. Austenitic stainless steel has low hardness and poor wear resistance. Low-temperature chemical treatment has insufficient thickness and may increase brittleness.

Method used

Use elements such as 镧 and 素 素 to enhance the corrosion resistance of stainless steel, and to form high -hardness martensite tissue through laser quenching. Essence

Benefits of technology

It significantly improves the corrosion resistance and hardness of the seamless thin -walled steel pipe of the stainless steel, prolonged the service life, and optimized the mechanical properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a stainless steel seamless thin-walled steel pipe and a preparation method thereof, and belongs to the technical field of seamless steel pipes. The present invention adds niobium and lanthanum to the raw material components to improve the corrosion resistance of the stainless steel pipe, and improves the uniformity of the material by heat treatment under different temperature conditions in the process, and improves the durability of the steel pipe by laser quenching. At the same time, a corrosion-resistant strengthening layer is added to the surface of the stainless steel seamless thin-walled steel pipe, and a polymer coating with excellent corrosion resistance is obtained through the joint action of polyacrylamide, modified hydroxyapatite, water-based polyurethane resin and other additives, thereby obtaining a stainless steel seamless thin-walled steel pipe with excellent corrosion resistance and mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of stainless steel seamless pipes and relates to a stainless steel seamless thin-walled pipe and a preparation method thereof. Background Art

[0002] Stainless steel materials must be used to prepare seamless steel pipes for transportation pipelines. However, there are too few stainless steel materials that have both high strength, high toughness and excellent corrosion resistance. Traditional ordinary carbon steel and low Cr alloy steel are difficult to meet the requirements.

[0003] At present, martensitic stainless steel and austenite-ferrite duplex stainless steel are commonly used to prepare high-strength seamless stainless steel pipes. Martensitic stainless steel has higher strength, hardness and wear resistance due to its higher carbon content, but its corrosion resistance is slightly poor. It is mainly used to prepare parts with high mechanical properties requirements and general corrosion resistance requirements. Its application in transportation pipelines is more limited.

[0004] Stainless steel pipes have the advantages of high strength, anti-aging, environmental friendliness and long service life. The thin-walled stainless steel is also conducive to reducing material consumption and reducing the cost of pipe manufacturing, transportation and installation.

[0005] There are many types of stainless steel. Currently, most stainless steel pipes use austenitic stainless steel. Although it has good oxidation resistance, corrosion resistance and mechanical properties, it has lower hardness and poorer wear resistance than other stainless steels, making it difficult to meet the requirements of pipelines for some special purposes. The use of low-temperature chemical treatment technology, such as low-temperature nitriding or carburizing to form an S-phase hardened layer on the surface, can enhance the surface hardness of austenitic stainless steel, improve its wear resistance, and avoid a decrease in corrosion resistance. However, in actual applications, it is found that the temperature of nitriding treatment is low and the diffusion rate of nitrogen atoms is slow, resulting in a thin hardened layer thickness and low load-bearing capacity. It may also increase the brittleness of stainless steel pipes. The corrosion resistance and hardness obtained by carburizing treatment are not as good as the hardened layer formed by the infiltration of nitrogen atoms, and the service life cannot be guaranteed. Summary of the invention

[0006] The object of the present invention is to provide a stainless steel seamless thin-walled steel pipe and a preparation method thereof, which has good corrosion resistance and hardness.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A stainless steel seamless thin-walled steel pipe, the surface of which has a corrosion-resistant strengthening layer, wherein the steel pipe comprises the following chemical components in weight percentage: Cr: 18.0-20.0%, Ni: 9.0-12.0%, Mo: 0.1-0.2%, N: 0.1-0.2%, Al: 1.3-1.6%, Mn: 1.8-2.0%, Si: 0.3-0.6%, P: 0.02-0.04%, C≤0.06%, Nb: 0.3-0.5%, La: 0.3-0.5%, and the balance is Fe and unavoidable impurities;

[0009] The corrosion-resistant strengthening layer is obtained by curing the following components in parts by mass: 2-5 parts of carbon nanotubes, 2-4 parts of tin oxide, 3-5 parts of modified hydroxyapatite, 3-5 parts of silicon nitride, 20-30 parts of polyacrylamide, 2-5 parts of waterborne polyurethane resin, 2-4 parts of crosslinking agent, 3-5 parts of dispersant, 2-4 parts of defoaming agent, and 20-30 parts of deionized water;

[0010] The preparation process of the modified hydroxyapatite is as follows:

[0011] 20-24 parts of silane coupling agent KH550 and 95-100 parts of succinic anhydride are mixed and uniformly dispersed in 100 parts of N,N-dimethylformamide DMF, and stirred for 2-3 hours, and then 18-23 parts of hydroxyapatite are added thereto, and after ultrasonic dispersion for 3-5 hours, the mixture is washed with ethanol and dried to obtain carboxylated hydroxyapatite;

[0012] Add 10-13 parts of carboxylated hydroxyapatite, 6-8 parts of epoxy resin and 0.5-0.7 parts of triphenylphosphine to 50-70 parts of DMF, mix thoroughly, heat to 55-70°C and react for 5-6 hours, filter and dry to obtain modified hydroxyapatite.

[0013] As a preferred technical solution of the present invention, the cross-linking agent is one of polypropylene glycol and polypropylene glycol glycidyl ether.

[0014] As a preferred technical solution of the present invention, the dispersant is one of carboxymethyl cellulose and hydroxyethyl cellulose.

[0015] As a preferred technical solution of the present invention, the defoaming agent is one of polydimethylsiloxane and polyoxyethylene polyoxypropanolamine ether.

[0016] A method for preparing a stainless steel seamless thin-walled steel pipe comprises the following steps:

[0017] S1. The raw materials of the stainless steel seamless thin-walled steel pipe are placed in a converter for primary refining for 5-6 hours at 1350-1400°C, and then heated to 1700-1750°C, kept warm for 2.5-3 hours for secondary smelting, and then refined in an AOD furnace at 1830-1900°C for 2-3 hours, and the obtained refined liquid is mold-cast into a steel billet;

[0018] S2. Under nitrogen protection, heat the steel billet in a heating furnace to 1280-1300°C, keep it warm for 6-8 hours, then raise the temperature to 1320-1350°C, keep it warm for 5-8 hours, and then cool it quickly;

[0019] S3, performing a perforation treatment on the heated steel billet by a hot rolling perforation method in a temperature range of 1180-1210°C to form a hollow tube billet;

[0020] S4, tempering the hollow tube blank, controlling the tempering time to be 2-3 hours, the temperature to be 790-820°C, and then air cooling;

[0021] S5. Apply a layer of lubricating oil on the surface of the tube blank, further deform the tube blank through cold rolling, perform sizing treatment, and then grind the surface of the tube blank;

[0022] S6, the sizing tube blank is kept at a temperature range of 1000-1090°C for 1-2 hours for solution annealing;

[0023] S7. Pickling and passivating the inside of the hollow tube with hydrochloric acid having a mass fraction of 15%;

[0024] S8. Under the protection of ammonia, laser quenching is performed on the tube blank;

[0025] S9, straightening the hollow tube blank to obtain a stainless steel tube;

[0026] S10, firstly perform sandblasting on the surface of the stainless steel pipe, uniformly coat the prepared corrosion-resistant strengthening layer coating material on the surface of the steel pipe by ultrasonic spraying, and then perform laser drying and curing to obtain the stainless steel seamless thin-walled steel pipe.

[0027] As a preferred technical solution of the present invention, in step S8, the laser quenching equipment is a semiconductor laser with a wavelength of about 980nm, a focal length of 345mm, a spot size of 17mmⅹ1.5mm, a laser output power of 1000~1100W, and a laser scanning rate of 4~5mm / s.

[0028] As a preferred technical solution of the present invention, in step S10, the preparation method of the corrosion-resistant strengthening layer coating raw material is: first, the carbon nanotubes, tin oxide, modified hydroxyapatite, and silicon nitride are crushed by a grinder and then passed through a 100-mesh sieve, and polyacrylamide, a cross-linking agent, an aqueous polyurethane resin and deionized water are fully mixed according to mass fractions, and then the modified hydroxyapatite and a dispersant are added, and after fully mixing, carbon nanotubes, tin oxide, silicon nitride, and a defoaming agent are continued to be added and mixed to obtain the prepared corrosion-resistant strengthening layer coating raw material.

[0029] As a preferred technical solution of the present invention, in step S10, the power of the ultrasonic spraying is 40-80 W, the ultrasonic frequency is 150-200 kHz, the continuous spraying volume is 600-1000 mL / h, and the spraying distance is 20-50 mm.

[0030] As a preferred technical solution of the present invention, in step S10, the power of the laser drying is 15-20 MW, and the drying time is 15-20 s.

[0031] In the present invention, surface treatment is first performed on hydroxyapatite, and hydroxyl groups on the surface react with a silane coupling agent to obtain Si-O-Si bonds, and the silane coupling agent is fixed on the surface of hydroxyapatite. In a solvent, succinic anhydride reacts with one end of the silane coupling agent that has not reacted with hydroxyapatite to obtain carboxylated hydroxyapatite. After a large number of carboxyl groups are introduced onto the surface of hydroxyapatite, under the action of triphenylphosphine, the epoxy groups in the epoxy resin are ring-opened, and the epoxy resin molecules are connected in series with the carboxylated hydroxyapatite via covalent bonds, thereby forming a cross-linked structure on the surface of hydroxyapatite. The hydroxyapatite modified by the epoxy resin forms an inorganic-organic hybrid composite structure, which can significantly improve the strength of the material and prevent the penetration of moisture and gas, thereby having stronger corrosion resistance.

[0032] Among them, epoxy resin has the advantages of high modulus, excellent corrosion resistance, good thermal stability, excellent bonding performance, etc. It contains a large number of active oxygen-containing groups. When preparing the coating, the hydroxyapatite modified by epoxy resin can be cross-linked with polyacrylamide through epoxy resin. Polyacrylamide is a high molecular polymer with good flocculation and is soluble in water. It can form a network structure at a lower concentration. The mechanical entanglement and hydrogen bonds between the chains together form network nodes to form a high polymer with a three-dimensional network structure. At the same time, the epoxy resin structure contains a large number of ether bonds and hydroxyl groups, which enhances the bonding strength between polymers. In addition, carbon nanotubes, tin oxide and silicon nitride are added as functional additives to further enhance the bonding strength between the coatings and improve the corrosion resistance of the bonding resin; and the viscosity and fluidity of polyacrylamide are improved by adding water-based polyurethane resin to improve the corrosion resistance of the coating.

[0033] In the present invention, niobium and lanthanum are added to the stainless steel raw material. The addition of niobium can significantly improve the corrosion resistance of the stainless steel. The oxide film formed by niobium can effectively prevent the migration of metal ions on the surface of the stainless steel, thereby protecting the stainless steel material from corrosion. Lanthanum has a modifier effect. When added to the steel, it reacts with the elements in the steel to form fine particles, which increases the nucleation rate during the casting cooling process, thereby achieving the effect of refining the grains, which helps to improve the mechanical properties of the stainless steel.

[0034] When preparing seamless thin-walled stainless steel pipes, the temperature is gradually increased to smelt the raw materials so that the components are completely mixed and evenly formed, and carbides are avoided between the components. The temperature inside and outside the tube blank is made consistent and uniform through heat treatment in a heating furnace, which can reduce deformation during subsequent hot rolling and piercing. It is then tempered at 790~820℃ to eliminate internal stress and brittleness.

[0035] Through laser quenching, the surface structure of the stainless steel seamless thin-walled steel pipe is changed to form a martensitic structure with high hardness. This structure can significantly improve the surface hardness and wear resistance of the steel pipe, thereby extending its service life.

[0036] Beneficial effects of the present invention:

[0037] The present invention adds niobium and lanthanum to the raw material components to improve the corrosion resistance of the stainless steel pipe, and improves the uniformity of the material through heat treatment under different temperature conditions in the process, and improves the durability of the steel pipe through laser quenching. At the same time, a corrosion-resistant strengthening layer is added to the surface of the stainless steel seamless thin-walled steel pipe, and a polymer coating with excellent corrosion resistance is obtained through the joint action of polyacrylamide, modified hydroxyapatite, water-based polyurethane resin and other additives, thereby obtaining a stainless steel seamless thin-walled steel pipe with excellent corrosion resistance. DETAILED DESCRIPTION

[0038] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0039] In the following examples and comparative examples:

[0040] The carbon nanotubes, tin oxide, modified hydroxyapatite and silicon nitride were crushed by a pulverizer and then passed through a 100-mesh sieve;

[0041] Silane coupling agent KH550: purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number: S15028-500mL;

[0042] Succinic anhydride: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., product number: S104823;

[0043] Hydroxyapatite: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: H766996;

[0044] Epoxy resin: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: R832312;

[0045] Triphenylphosphine: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., product number: T104478;

[0046] Polyacrylamide: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., product number: P108471;

[0047] Polypropylene glycol: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: P815575;

[0048] Waterborne polyurethane resin: purchased from Shenzhen Jitian Chemical Co., Ltd., model: F0401;

[0049] Carboxymethyl cellulose: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: C889437;

[0050] Carbon nanotubes: purchased from Zhengzhou Huiju Chemical Co., Ltd., product number: A068566;

[0051] Tin oxide: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: S817638;

[0052] Silicon nitride: purchased from Tianjin Xiensi Biochemical Technology Co., Ltd., product number: S-15090;

[0053] Polydimethylsiloxane: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: P822627;

[0054] Polypropylene glycol glycidyl ether: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: 768750. Example

[0055] The steel pipe includes the following chemical compositions in weight percentage: Cr: 18.0%, Ni: 9.0%, Mo: 0.1%, N: 0.1%, Al: 1.3%, Mn: 1.8%, Si: 0.3%, P: 0.02%, C: 0.06%, Nb: 0.3%, La: 0.3%, the balance being Fe and unavoidable impurities;

[0056] The preparation process of modified hydroxyapatite is:

[0057] 20 parts of silane coupling agent KH550 and 95 parts of succinic anhydride were mixed and uniformly dispersed in 100 parts of N, N-dimethylformamide, and stirred for 2 hours, and then 18 parts of hydroxyapatite were added thereto, and ultrasonically dispersed for 3 hours, and then washed with ethanol and dried to obtain carboxylated hydroxyapatite;

[0058] 10 parts of carboxylated hydroxyapatite, 6 parts of epoxy resin and 0.5 parts of triphenylphosphine were added to 50 parts of DMF, mixed thoroughly, heated to 55° C. and reacted for 6 hours, filtered and dried to obtain modified hydroxyapatite.

[0059] The preparation method of the corrosion-resistant strengthening layer coating raw material is as follows:

[0060] After 20 parts of polyacrylamide, 2 parts of polypropylene glycol, 2 parts of water-based polyurethane resin and 20 parts of deionized water are fully mixed, 3 parts of modified hydroxyapatite and 3 parts of carboxymethyl cellulose are added and fully mixed, and then 2 parts of carbon nanotubes, 2 parts of tin oxide, 3 parts of silicon nitride and 2 parts of polydimethylsiloxane are added and mixed to obtain the prepared corrosion-resistant strengthening layer coating raw material.

[0061] Preparation of stainless steel seamless thin-walled steel pipe:

[0062] S1. The raw materials of the stainless steel seamless thin-walled steel pipe are placed in a converter for primary refining for 5 hours at 1350°C, and then heated to 1700°C, kept warm for 2.5 hours for secondary smelting, and then refined in an AOD furnace at 1830°C for 2 hours, and the obtained refined liquid is mold-cast into a steel billet;

[0063] S2. Under nitrogen protection, heat the steel billet to 1280°C in a heating furnace, keep it warm for 6 hours, then raise the temperature to 1320°C, keep it warm for 5 hours, and then cool it quickly;

[0064] S3, performing a perforation treatment on the heated steel billet by a hot rolling perforation method at 1180° C. to form a hollow tube billet;

[0065] S4, tempering the hollow tube blank, controlling the tempering time to be 2h, the temperature to be 790°C, and then air cooling;

[0066] S5. Apply a layer of lubricating oil on the surface of the tube blank, further deform the tube blank through cold rolling, perform sizing treatment, and then grind the surface of the tube blank;

[0067] S6, the sizing tube blank is kept at 1000°C for 1 hour for solution annealing;

[0068] S7. Pickling and passivating the inside of the hollow tube with hydrochloric acid having a mass fraction of 15%;

[0069] S8. Under the protection of ammonia, the tube blank is laser quenched. The laser quenching equipment is a semiconductor laser with a wavelength of about 980nm, a focal length of 345mm, a spot size of 17mm x 1.5mm, a laser output power of 1000W, and a laser scanning rate of 4mm / s.

[0070] S9, straightening the hollow tube blank to obtain a stainless steel tube;

[0071] S10. First, the surface of the stainless steel pipe is sandblasted, and the prepared corrosion-resistant strengthening layer coating raw material is evenly coated on the surface of the steel pipe by ultrasonic spraying, and then dried and cured by a 15MW laser for 15s to obtain the stainless steel seamless thin-walled steel pipe, wherein the power of the ultrasonic spraying is 40W, the ultrasonic frequency is 150kHz, the continuous spraying amount is 600mL / h, and the spraying distance is 20mm. Example

[0072] The steel pipe includes the following chemical compositions in weight percentage: Cr: 19.0%, Ni: 10.0%, Mo: 0.15%, N: 0.15%, Al: 1.5%, Mn: 1.9%, Si: 0.4%, P: 0.03%, C: 0.04%, Nb: 0.4%, La: 0.4%, the balance being Fe and unavoidable impurities;

[0073] The preparation process of modified hydroxyapatite is:

[0074] 22 parts of silane coupling agent KH550 and 96 parts of succinic anhydride were mixed and uniformly dispersed in 100 parts of N, N-dimethylformamide, and stirred for 2.5 hours, and then 19 parts of hydroxyapatite were added thereto. After ultrasonic dispersion for 4 hours, the mixture was washed with ethanol and dried to obtain carboxylated hydroxyapatite;

[0075] 12 parts of carboxylated hydroxyapatite, 7 parts of epoxy resin and 0.6 parts of triphenylphosphine were added to 60 parts of DMF, mixed thoroughly, heated to 60° C. and reacted for 5.5 hours, filtered and dried to obtain modified hydroxyapatite.

[0076] The preparation method of the corrosion-resistant strengthening layer coating raw material is as follows:

[0077] After 25 parts of polyacrylamide, 3 parts of polypropylene glycol glycidyl ether, 4 parts of waterborne polyurethane resin and 25 parts of deionized water are fully mixed, 4 parts of modified hydroxyapatite and 4 parts of carboxymethyl cellulose are added and fully mixed, and then 4 parts of carbon nanotubes, 3 parts of tin oxide, 4 parts of silicon nitride and 3 parts of polydimethylsiloxane are added and mixed to obtain the prepared corrosion-resistant strengthening layer coating raw material.

[0078] Preparation of stainless steel seamless thin-walled steel pipe:

[0079] S1. At 1370°C, the raw materials of the stainless steel seamless thin-walled steel pipe are placed in a converter for primary refining for 5.5 hours, and then heated to 1720°C, kept warm for 2.5 hours for secondary smelting, and then refined in an AOD furnace at 1850°C for 2 hours, and the obtained refined liquid is mold-cast into a steel billet;

[0080] S2. Under nitrogen protection, heat the steel billet to 1290°C in a heating furnace, keep it warm for 7 hours, then raise the temperature to 1330°C, keep it warm for 6 hours, and then cool it quickly;

[0081] S3, at 1190°C, the heated steel billet is pierced by hot rolling piercing to form a hollow tube billet;

[0082] S4, tempering the hollow tube blank, controlling the tempering time to be 2.5h, the temperature to be 800°C, and then air cooling;

[0083] S5. Apply a layer of lubricating oil on the surface of the tube blank, further deform the tube blank through cold rolling, perform sizing treatment, and then grind the surface of the tube blank;

[0084] S6, the sized tube is kept at 1050°C for 1.5h for solution annealing;

[0085] S7. Pickling and passivating the inside of the hollow tube with hydrochloric acid having a mass fraction of 15%;

[0086] S8. Under the protection of ammonia, the tube blank is laser quenched. The laser quenching equipment is a semiconductor laser with a wavelength of about 980nm, a focal length of 345mm, a spot size of 17mm x 1.5mm, a laser output power of 1050W, and a laser scanning rate of 4mm / s.

[0087] S9, straightening the hollow tube blank to obtain a stainless steel tube;

[0088] S10. First, the surface of the stainless steel pipe is sandblasted, and the prepared corrosion-resistant strengthening layer coating raw material is evenly coated on the surface of the steel pipe by ultrasonic spraying, and then dried and cured by a 17MW laser for 15s to obtain the stainless steel seamless thin-walled steel pipe, wherein the power of the ultrasonic spraying is 60W, the ultrasonic frequency is 170kHz, the continuous spraying amount is 800mL / h, and the spraying distance is 30mm. Example

[0089] The steel pipe includes the following chemical compositions in weight percentage: Cr: 20.0%, Ni: 12.0%, Mo: 0.2%, N: 0.2%, Al: 1.6%, Mn: 2.0%, Si: 0.6%, P: 0.04%, C: 0.03%, Nb: 0.5%, La: 0.5%, the balance being Fe and unavoidable impurities;

[0090] The preparation process of the modified hydroxyapatite is as follows:

[0091] 24 parts of silane coupling agent KH550 and 100 parts of succinic anhydride were mixed and uniformly dispersed in 100 parts of DMF. After stirring for 3 hours, 23 parts of hydroxyapatite were added thereto. After ultrasonic dispersion for 5 hours, the mixture was washed with ethanol and dried to obtain carboxylated hydroxyapatite.

[0092] 13 parts of carboxylated hydroxyapatite, 8 parts of epoxy resin and 0.7 parts of triphenylphosphine were added to 70 parts of DMF, mixed thoroughly, heated to 70° C. and reacted for 6 hours, filtered and dried to obtain modified hydroxyapatite.

[0093] The preparation method of the corrosion-resistant strengthening layer coating raw material is as follows:

[0094] After 30 parts of polyacrylamide, 4 parts of polypropylene glycol, 5 parts of waterborne polyurethane resin and 30 parts of deionized water are fully mixed, 5 parts of modified hydroxyapatite and 5 parts of carboxymethyl cellulose are added and fully mixed, and then 5 parts of carbon nanotubes, 4 parts of tin oxide, 5 parts of silicon nitride and 4 parts of polydimethylsiloxane are added and mixed to obtain the prepared corrosion-resistant strengthening layer coating raw material.

[0095] Preparation of stainless steel seamless thin-walled steel pipe:

[0096] S1. The raw materials of the seamless stainless steel tube are placed in a converter for primary refining for 6 hours at 1400°C, then heated to 1750°C, kept warm for 3 hours for secondary smelting, and then refined in an AOD furnace at 1900°C for 3 hours, and the obtained refined liquid is mold-cast into a billet;

[0097] S2. Under nitrogen protection, heat the steel billet to 1300°C in a heating furnace, keep it warm for 8 hours, then raise the temperature to 1350°C, keep it warm for another 8 hours, and then cool it quickly;

[0098] S3, performing a perforation treatment on the heated steel billet by a hot rolling perforation method at a temperature of 1210° C. to form a hollow tube billet;

[0099] S4, tempering the hollow tube blank, controlling the tempering time to be 2-3 hours, the temperature to be 790-820°C, and then air cooling;

[0100] S5. Apply a layer of lubricating oil on the surface of the tube blank, further deform the tube blank through cold rolling, perform sizing treatment, and then grind the surface of the tube blank;

[0101] S6, the sized tube is kept at 1090°C for 2h for solution annealing;

[0102] S7. Pickling and passivating the inside of the hollow tube with hydrochloric acid having a mass fraction of 15%;

[0103] S8. Under the protection of ammonia, the tube blank is laser quenched. The laser quenching equipment is a semiconductor laser with a wavelength of about 980nm, a focal length of 345mm, a spot size of 17mm x 1.5mm, a laser output power of 1100W, and a laser scanning rate of 5mm / s.

[0104] S9, straightening the hollow tube blank to obtain a stainless steel tube;

[0105] S10. First, the surface of the stainless steel pipe is sandblasted, and the prepared corrosion-resistant strengthening layer coating raw material is evenly coated on the surface of the steel pipe by ultrasonic spraying, and then dried and cured by a 20MW laser for 20s to obtain the stainless steel seamless thin-walled steel pipe, wherein the power of the ultrasonic spraying is 80W, the ultrasonic frequency is 200kHz, the continuous spraying amount is 1000mL / h, and the spraying distance is 50mm.

[0106] Comparative Example 1

[0107] The difference between Comparative Example 1 and Example 1 is that the hydroxyapatite in Comparative Example 1 is modified, and the other operations are the same.

[0108] Comparative Example 2

[0109] The difference between Comparative Example 2 and Example 1 is that no modified hydroxyapatite is added in Comparative Example 2, and the other operations are the same.

[0110] Comparative Example 3

[0111] The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, no corrosion-resistant strengthening layer is added to the surface of the steel pipe, and the other operations are the same.

[0112] Comparative Example 4

[0113] The difference between Comparative Example 4 and Example 1 is that no niobium is added in Comparative Example 4, and the steel pipe includes the following chemical components in weight percentage: Cr: 18.0%, Ni: 9.0%, Mo: 0.1%, N: 0.1%, Al: 1.3%, Mn: 1.8%, Si: 0.3%, P: 0.02%, C: 0.06%, La: 0.1%, and the balance is Fe and unavoidable impurities, and the other operations are the same.

[0114] Comparative Example 5

[0115] The difference between Comparative Example 5 and Example 1 is that no lanthanum is added in Comparative Example 5, and the other operations are the same. The steel pipe includes the following chemical components in weight percentage: Cr: 18.0%, Ni: 9.0%, Mo: 0.1%, N: 0.1%, Al: 1.3%, Mn: 1.8%, Si: 0.3%, P: 0.02%, C: 0.06%, Nb: 0.1%, La: 0.1%, and the balance is Fe and unavoidable impurities.

[0116] Performance Test:

[0117] 1. Mechanical properties test was carried out according to standard GB / T 228.1-2021. The results are shown in Table 1:

[0118] Table 1

[0119] Tensile strength / MPa Elongation after break (%) Example 1 653 61 Example 2 655 63 Example 3 657 65 Comparative Example 1 622 56 Comparative Example 2 603 52 Comparative Example 3 584 49 Comparative Example 4 626 57 Comparative Example 5 628 58

[0120] 2. The steel pipes prepared in Examples 1-3 of the present invention and Comparative Examples 1-5 were subjected to corrosion resistance tests. The coating layer thickness was 500 μm. The blue dot method test was performed in accordance with GB / T25150-2010. The test results are shown in Table 2.

[0121] Table 2

[0122] Group Resistant to 5% neutral salt spray, 720h Resistant to 5% sulfuric acid, 720h Resistant to 5% sodium hydroxide, 720h Example 1 No bubbles, no rust No bubbles, no rust No bubbles, no rust Example 2 No bubbles, no rust No bubbles, no rust No bubbles, no rust Example 3 No bubbles, no rust No bubbles, no rust No bubbles, no rust Comparative Example 1 Bubbles appear and 1% of the steel pipe surface is rusted Bubbles appear and 1% of the steel pipe surface is rusted Bubbles appear and 1% of the steel pipe surface is rusted Comparative Example 2 Bubbles appear and 2% of the steel pipe surface is rusted Bubbles appear and 2% of the steel pipe surface is rusted Bubbles appear and 1% of the steel pipe surface is rusted Comparative Example 3 6% of the steel pipe surface area has bubbles and rust 8% of the steel pipe surface area has bubbles and rust 8% of the steel pipe surface area has bubbles and rust Comparative Example 4 No bubbles, no rust No bubbles, no rust Bubbles appear and 0.2% of the steel pipe surface is rusted Comparative Example 5 No bubbles, no rust Bubbles appear and 0.3% of the steel pipe surface area is rusted No bubbles, no rust

[0123] It can be seen from Table 1-2 that the stainless steel seamless thin-walled steel pipe prepared by the present invention has good corrosion resistance and mechanical strength. The corrosion-resistant strengthening coating applied on the surface can delay the corrosion probability of the steel pipe, increase the service life of the steel pipe, and is better than the performance of comparative examples 1-5.

[0124] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A stainless steel seamless thin-walled steel pipe, characterized in that: The surface of the stainless steel seamless thin-walled steel pipe has a corrosion-resistant strengthening layer, wherein the steel pipe comprises the following chemical components in weight percentage: Cr: 18.0-20.0%, Ni: 9.0-12.0%, Mo: 0.1-0.2%, N: 0.1-0.2%, Al: 1.3-1.6%, Mn: 1.8-2.0%, Si: 0.3-0.6%, P: 0.02-0.04%, C≤0.06%, Nb: 0.3-0.5%, La: 0.3-0.5%, and the balance is Fe and unavoidable impurities; The corrosion-resistant strengthening layer is obtained by curing the following components in parts by mass: 2-5 parts of carbon nanotubes, 2-4 parts of tin oxide, 3-5 parts of modified hydroxyapatite, 3-5 parts of silicon nitride, 20-30 parts of polyacrylamide, 2-5 parts of waterborne polyurethane resin, 2-4 parts of crosslinking agent, 3-5 parts of dispersant, 2-4 parts of defoaming agent, and 20-30 parts of deionized water; The preparation process of the modified hydroxyapatite is as follows: 20-24 parts of silane coupling agent KH550 and 95-100 parts of succinic anhydride are mixed and uniformly dispersed in 100 parts of N,N-dimethylformamide DMF, and stirred for 2-3 hours, and then 18-23 parts of hydroxyapatite are added thereto, and after ultrasonic dispersion for 3-5 hours, the mixture is washed with ethanol and dried to obtain carboxylated hydroxyapatite; Add 10-13 parts of carboxylated hydroxyapatite, 6-8 parts of epoxy resin and 0.5-0.7 parts of triphenylphosphine to 50-70 parts of DMF, mix thoroughly, heat to 55-70°C and react for 5-6 hours, filter and dry to obtain modified hydroxyapatite.

2. The stainless steel seamless thin-walled steel pipe according to claim 1, characterized in that: The cross-linking agent is one of polypropylene glycol and polypropylene glycol glycidyl ether.

3. The stainless steel seamless thin-walled steel pipe according to claim 1, characterized in that: The dispersant is one of carboxymethyl cellulose and hydroxyethyl cellulose.

4. The stainless steel seamless thin-walled steel pipe according to claim 1, characterized in that: The defoaming agent is one of polydimethylsiloxane and polyoxyethylene polyoxypropanolamine ether.

5. A method for preparing a stainless steel seamless thin-walled steel pipe according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. The raw materials of the stainless steel seamless thin-walled steel pipe are placed in a converter for primary refining for 5-6 hours at 1350-1400°C, and then heated to 1700-1750°C, kept warm for 2.5-3 hours for secondary smelting, and then refined in an AOD furnace at 1830-1900°C for 2-3 hours, and the obtained refined liquid is mold-cast into a steel billet; S2. Under nitrogen protection, heat the steel billet in a heating furnace to 1280-1300°C, keep it warm for 6-8 hours, then raise the temperature to 1320-1350°C, keep it warm for 5-8 hours, and then cool it quickly; S3, performing a perforation treatment on the heated steel billet by a hot rolling perforation method in a temperature range of 1180-1210°C to form a hollow tube billet; S4, tempering the hollow tube blank, controlling the tempering time to be 2-3 hours, the temperature to be 790-820°C, and then air cooling; S5. Apply a layer of lubricating oil on the surface of the tube blank, further deform the tube blank through cold rolling, perform sizing treatment, and then grind the surface of the tube blank; S6, the sizing tube blank is kept at a temperature range of 1000-1090°C for 1-2 hours for solution annealing; S7. Pickling and passivating the inside of the hollow tube with hydrochloric acid having a mass fraction of 15%; S8. Under the protection of ammonia, laser quenching is performed on the tube blank; S9, straightening the hollow tube blank to obtain a stainless steel tube; S10, firstly perform sandblasting on the surface of the stainless steel pipe, uniformly coat the prepared corrosion-resistant strengthening layer coating material on the surface of the steel pipe by ultrasonic spraying, and then perform laser drying and curing to obtain the stainless steel seamless thin-walled steel pipe.

6. The stainless steel seamless thin-walled steel pipe according to claim 5, characterized in that: In step S8, the laser quenching equipment is a semiconductor laser with a wavelength of 980nm, a focal length of 345mm, a spot size of 17mmⅹ1.5mm, a laser output power of 1000~1100W, and a laser scanning rate of 4~5mm / s.

7. The stainless steel seamless thin-walled steel pipe according to claim 5, characterized in that: In step S10, the preparation method of the corrosion-resistant strengthening layer coating raw material is: first, the carbon nanotubes, tin oxide, modified hydroxyapatite, and silicon nitride are crushed by a grinder and then passed through a 100-mesh sieve, and then polyacrylamide, a cross-linking agent, an aqueous polyurethane resin and deionized water are fully mixed according to the mass fraction, and then the modified hydroxyapatite and a dispersant are added. After being fully mixed, carbon nanotubes, tin oxide, silicon nitride, and a defoaming agent are continued to be added and mixed to obtain the prepared corrosion-resistant strengthening layer coating raw material.

8. The stainless steel seamless thin-walled steel pipe according to claim 5, characterized in that: In step S10, the power of the ultrasonic spraying is 40-80 W, the ultrasonic frequency is 150-200 kHz, the continuous spraying volume is 600-1000 mL / h, and the spraying distance is 20-50 mm.

9. The stainless steel seamless thin-walled steel pipe according to claim 5, characterized in that: In step S10, the power of the laser drying is 15-20 MW, and the drying time is 15-20 s.

Citation Information

Patent Citations

  • Ultra-low-carbon austenite seamless stainless steel tube and preparation method for seamless stainless steel tube

    CN106367694A

  • Anticorrosive fireproof coating specially used for steel structures and preparation method thereof

    CN107163815A